Comparative Studies on Ganoderma (Karst.) from Infected Oil Palm and Coconut Stumps with Special Reference to Their Morphological, Molecular and Isozyme Characteristics - Zakaria, Latiffah (2001)
The basal stem rot of oil palm caused by Ganoderma i s the most serious disease infecting oil palm in South-east Asia. It is believed that coconut stumps which are colonized by Ganoderma can act as sources of inoculum for i nfection to healthy palms through root contact. However, it is not known whether the Ganoderma infecting oil palm and those colonizing coconut stumps are the same species. Therefore, a comparative study was conducted to determine the similarities and differences between Ganoderma isolates from infected oil palm and coconut stumps, using a multidisciplinary approaches in which morphological. biochemical (intracellular and extracellular enzyme systems) and molecular characteristics (RAPD, RAMS, RFLP and direct sequencing of the ITS regions + 5 . 8 S gene of rDNA) were analysed. Based on the morphological characteristics of the basidiomata, Ganoderma from infected oil palm and coconut stumps conformed to the description of G. boninense in Steyaert's classification system for Ganoderma ( 1 967 and 1975 ). The growth on various media and at different temperatures, and the cultural characteristics of the isolates from infected oil palm and coconut stumps were similar with no significant difference observed between the two groups of Ganoderma. However, the isolates were somatically incompatible with one another, which indicated that they were genotypically distinct individuals and not clones of a genotypic individual. The isozyme profiles from intracellular and extracellular enzyme systems, and the DNA profiles from RAPD, RAMS and RFLP of the ITS regions + 5 . 8 S gene revealed that Ganoderma isolates from infected oil palm and coconut stumps were very variable. Nucleotide sequences of the ITS regions + 5 . 8 S gene of rDNA from a limited number of isolates also showed that the isolates from both groups of Ganoderma were very variable. The Southern hybridization of RAMS gel showed that labelled probes from oil palm and coconut hybridized to the common bands of 1 .2 kb by from primer (CGA)5 and 1 .4 kb band by primer (ACA)5 which indicated that the bands of the same molecular sizes are likely to be homologous. Cluster analysis based on data from biochemical and molecular characters, and phylogenetic analysis of the nucleotide sequence showed that the oil palm isolates and the coconut isolates did not cluster separately which indicated that isolates of both groups of Ganoderma are closely related.